Cercarial dermatitis, a neglected allergic disease - Kolářová, Libuše; Horák, Petr; Skírnisson, Karl; Marečková, Helena; Doenhoff, Michael (Clinical reviews in allergy & immunology, 2013)
Cercarial dermatitis (swimmer's itch) is a common non-communicable water-borne disease. It is caused by penetration of the skin by larvae (cercariae) of schistosomatid flukes and develops as a maculopapular skin eruption after repeated contacts with the parasites. The number of outbreaks of the disease is increasing, and cercarial dermatitis can therefore be considered as an emerging problem. Swimmer's itch is mostly associated with larvae of the bird schistosomes of Trichobilharzia spp. Recent results have shown that mammalian infections (including man) manifest themselves as an allergic reaction which is able to trap and eliminate parasites in the skin. Studies on mammals experimentally infected by bird schistosome cercariae revealed, however, that during primary infection, parasites are able to escape from the skin to the lungs or central nervous system. This review covers basic information on detection of the infectious agents in the field and the clinical course of the disease, including other pathologies which may develop after infection by cercariae, and diagnosis of the disease.
Keywords: dermatitida; schistosomóza; lidé; Cercaria; Schistosomiasis; plavání; Central Nervous System; Schistosoma; Humans; Swimming; centrální nervový systém; Skin; Disease Models, Animal; zvířata; kůže; cerkárie; Animals; Dermatitis; Lung; modely nemocí na zvířatech; plíce